Asphalt-based hard carbon negative electrode material as well as preparation method and application thereof

The asphalt is oxidized by atomic vapor deposition to form a crosslinked structure and dopant nitrogen atoms, which solves the problems of low sodium storage capacity and complex preparation process of asphalt-based hard carbon negative electrode materials, and achieves high-efficiency and low-cost asphalt-based hardness The preparation of carbon anode material improves the performance and production convenience of sodium ion batteries.

CN119160874AActive Publication Date: 2024-12-20WUHAN BISIDI BATTERY MATERIAL CO LTD

Patent Information

Application Number
CN202411321501.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-20
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Traditional oxidation methods cannot quickly and uniformly oxidize asphalt, resulting in low sodium storage capacity of the prepared asphalt-based hard carbon negative electrode material, and the existing preparation process is complex, with high factory production and high cost, which affects its promotion and application.

Method used

The asphalt powder is oxidized by atomic vapor deposition method, and the cycle repeats between inert gas and ozone is repeated to form a cross-linked structure, which inhibits the rearrangement of asphalt during high-temperature carbonization, and optionally doped nitrogen atoms to form a more complex network. simplifies process and reduces costs.

Benefits of technology

It realizes rapid and uniform oxidation of asphalt-based hard carbon negative electrode materials, improves sodium storage function and electrochemical performance, simplifies the preparation process, reduces costs, is suitable for industrial production and promotion applications, and significantly improves the reversible capacity and circulation of sodium ion batteries. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160874A_ABST
    Figure CN119160874A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery material preparation, and particularly relates to an asphalt-based hard carbon negative electrode material and a preparation method and application thereof. According to the method, the asphalt powder is placed in the reaction chamber, then the inert gas and the ozone are sequentially introduced and circularly repeated, the asphalt is subjected to oxidation treatment by adopting the atomic vapor deposition method, direct crosslinking is carried out by using the ozone, and a crosslinking structure is formed among the asphalt, so that uniform oxidation of the asphalt can be ensured, rearrangement of the asphalt in the subsequent carbonization process is inhibited, and the carbonization quality of the asphalt is improved. Disordered hard carbon can be obtained, so that the sodium storage function and the electrochemical performance of the asphalt-based hard carbon negative electrode material are improved. Compared with an existing preparation method, the preparation method has the advantages that rapid and uniform oxidation of the asphalt can be realized, other heteroatoms are not introduced, additional elution and impurity removal processes are not needed, the preparation method has the advantages of simple process, simplicity and convenience in operation, low cost and the like, industrial production, popularization and application are facilitated, and convenience is provided for the structure-function relationship of the asphalt-based hard carbon negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery material preparation, and more specifically, relates to an asphalt-based hard carbon negative electrode material, a preparation method thereof, and an application thereof. Background Art

[0002] Hard carbon materials are widely used in sodium ion batteries or lithium ion batteries due to their advantages such as high capacity, low sodium insertion potential and good cycle stability. There are many types of precursors for preparing hard carbon, including biomass, resin, polymer, asphalt, anthracite, etc. Among them, asphalt has a high carbon yield, abundant raw material sources and low cost, making it an ideal precursor for preparing hard carbon materials. However, asphalt is very easy to pyrolyze and graphitize during high-temperature carbonization, forming a soft carbon material with small interlayer spacing, few defects and low sodium storage capacity. Pre-oxidation and cross-linking of asphalt are effective methods to inhibit the graphitization of asphalt during high-temperature carbonization, but traditional oxidation methods cannot achieve rapid and uniform oxidation of asphalt, and the prepared oxidized asphalt cannot meet the needs of high-capacity sodium storage after carbonization.

[0003] In addition, the preparation process of most asphalt-based hard carbon negative electrode materials is complicated. For example, the preparation process of patent document CN117776148A requires the addition of a template to reduce the size of the asphalt carbon skeleton, shorten the oxidation path of the asphalt, shorten the oxidation cross-linking time and improve the oxidation cross-linking effect. In addition, it also involves pickling, drying, crushing, screening and other processes. The preparation process of patent document CN118289737A involves dispersing oxidized asphalt, functional additives and hard carbon precursors in a solvent, removing the solvent to regulate the pore structure and cycle stability of the hard carbon. Its preparation process is complicated, and it is difficult to carry out factory production. In addition, a certain amount of hard carbon precursors need to be added, which will increase the preparation cost and is not conducive to promotion and application. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of this application is to provide an asphalt-based hard carbon negative electrode material, its preparation method and application, aiming to solve the problems that traditional oxidation methods cannot quickly and evenly oxidize asphalt, and the prepared asphalt-based hard carbon negative electrode material has low sodium storage capacity.

[0005] To achieve the above object, the present application provides a method for preparing a pitch-based hard carbon negative electrode material, comprising the following steps:

[0006] S1. placing asphalt powder in a reaction chamber, then introducing inert gas and ozone in turn and repeating the cycle, oxidizing the asphalt powder by atomic vapor deposition to obtain an oxidized precursor;

[0007] S2. Carbonizing the above-mentioned oxidative precursor in a protective atmosphere to obtain a pitch-based hard carbon negative electrode material.

[0008] Preferably, the oxidation precursor is a heteroatom-doped oxidation precursor, and the heteroatom includes nitrogen atoms.

[0009] Preferably, the heteroatom further includes at least one of a sulfur atom and a phosphorus atom.

[0010] Preferably, the method for preparing the heteroatom-doped oxidative precursor comprises the following steps:

[0011] S11, introducing inert gas to clean the reaction environment;

[0012] S12, introducing ozone;

[0013] S13, introducing an inert gas carrying a heteroatom compound;

[0014] S14. Repeat steps S11, S12 and S13 in sequence to achieve uniform oxidation and heteroatom doping of the asphalt powder, and obtain a heteroatom-doped oxidation precursor, in which the mass percentage of nitrogen atoms is 0.1% to 0.5%.

[0015] Preferably, in step S13, the heteroatom compound includes one or more of urea, ammonium citrate, dopamine, amino acid, cyanamide, dicyanamide, melamine and cyanuric acid.

[0016] Preferably, in step S14, the mass percentage of nitrogen atoms in the heteroatom-doped oxidized precursor is 0.1% to 0.4%.

[0017] Preferably, in step S1, the particle size of the asphalt powder is 5 μm to 20 μm.

[0018] Preferably, in step S1, the temperature of the oxidation treatment is 200°C to 400°C.

[0019] Preferably, in step S2, the gas of the protective atmosphere is one or more of nitrogen, argon, neon, helium, xenon or krypton.

[0020] Preferably, in step S1, the temperature of the carbonization treatment is 1100° C. to 1700° C., and the time of the carbonization treatment is 1 h to 5 h.

[0021] On the other hand, the present application also provides a asphalt-based hard carbon negative electrode material, which is prepared by the above-mentioned preparation method.

[0022] The present application also provides the use of the above-mentioned asphalt-based hard carbon negative electrode material in the preparation of sodium ion battery negative electrode material.

[0023] The present application also provides a battery, which includes a positive electrode and a negative electrode, and the negative electrode includes the above-mentioned asphalt-based hard carbon negative electrode material.

[0024] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art:

[0025] (1) The preparation method of the asphalt-based hard carbon negative electrode material provided in the present application is to place the asphalt powder in a reaction chamber, and then introduce inert gas and ozone in turn and repeat the cycle, and oxidize the asphalt powder by atomic vapor deposition, and directly cross-link with ozone to form a cross-linked structure between the asphalts, which can ensure the uniform oxidation of the asphalt, inhibit the rearrangement of the asphalt during the subsequent carbonization treatment, and obtain disordered hard carbon, thereby improving the sodium storage function and electrochemical performance of the asphalt-based hard carbon negative electrode material. Compared with the existing preparation method, the present application can achieve rapid and uniform oxidation of asphalt, without introducing other heteroatoms, and without the need for additional elution and impurity removal processes. It has the advantages of simple process, simple operation, low cost, etc., which is convenient for industrial production and promotion and application, and at the same time provides convenience for the structure-activity relationship of asphalt-based hard carbon negative electrode materials.

[0026] (2) In a preferred embodiment, the present application uses atomic vapor deposition to oxidize the asphalt while doping heteroatoms, so that the oxidation precursor forms a more complex network structure, effectively inhibiting the rearrangement of the asphalt during the carbonization process, thereby significantly improving the sodium storage function of the asphalt-based hard carbon negative electrode material. When the above-mentioned asphalt-based hard carbon negative electrode material is applied to sodium ion batteries, the reversible capacity of the battery can be significantly improved, and it has the advantages of high platform capacity and stable cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a flow chart of the preparation method of the pitch-based hard carbon negative electrode material provided in the present application;

[0028] Figure 2 It is the charge and discharge curve of the battery assembled in Example 1 of the present application. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0030] The present application provides a method for preparing a pitch-based hard carbon negative electrode material, such as Figure 1 As shown, the following steps are included:

[0031] S1. placing asphalt powder in a reaction chamber, then introducing inert gas and ozone in turn and repeating the cycle, oxidizing the asphalt powder by atomic vapor deposition to obtain an oxidized precursor;

[0032] S2. Carbonizing the above-mentioned oxidative precursor in a protective atmosphere to obtain a pitch-based hard carbon negative electrode material.

[0033] In some embodiments, in step S1, the method for preparing the oxidation precursor comprises the following steps:

[0034] S11, introducing inert gas to clean the reaction environment;

[0035] S12, introducing ozone;

[0036] S13. Repeat steps S11 and S12 in sequence to achieve uniform oxidation of the asphalt powder and obtain an oxidized precursor.

[0037] It is understandable that those skilled in the art can reasonably select the time for introducing the inert gas in step S11, the time for introducing ozone in step S12, and the number of times to repeat steps S11 and S12 in sequence according to actual conditions, such as the capacity of the cavity of the atomic layer deposition equipment, the processing volume of asphalt powder, etc. As long as uniform oxidation of the asphalt powder can be achieved, it is within the scope of protection of this application.

[0038] In some embodiments, in step S1, typically and non-limitingly, the parameters for preparing the oxidation precursor by atomic vapor deposition may be:

[0039] S11, introducing inert gas for 40 seconds to 80 seconds to clean the reaction environment;

[0040] S12, introduce ozone for 100 to 150 seconds;

[0041] S13. Repeat steps S11 and S12 10 to 100 times in sequence to achieve uniform oxidation of the asphalt powder and obtain an oxidized precursor.

[0042] In some embodiments, in step S1, the oxidation precursor is a heteroatom-doped oxidation precursor, and the heteroatom includes a nitrogen atom.

[0043] In some embodiments, the heteroatom further includes at least one of a sulfur atom and a phosphorus atom.

[0044] In some embodiments, in step S1, the method for preparing the heteroatom-doped oxidized precursor comprises the following steps:

[0045] S11, introducing inert gas to clean the reaction environment;

[0046] S12, introducing ozone;

[0047] S13, introducing an inert gas carrying a heteroatom compound;

[0048] S14. Repeat steps S11, S12 and S13 in sequence to achieve uniform oxidation and heteroatom doping of the asphalt powder, and obtain a heteroatom-doped oxidation precursor, in which the mass percentage of nitrogen atoms is 0.1% to 0.5%.

[0049] In some embodiments, in step S1, typically and non-limitingly, the parameters for preparing the heteroatom-doped oxidized precursor by atomic vapor deposition may be:

[0050] S11, introducing inert gas for 40 seconds to 80 seconds to clean the reaction environment;

[0051] S12, introduce ozone for 100 to 150 seconds;

[0052] S13, introducing an inert gas carrying a heteroatom compound for 2 seconds to 20 seconds;

[0053] S14. Repeat steps S11, S12 and S13 10 to 100 times in sequence to achieve uniform oxidation and heteroatom doping of the asphalt powder and obtain a heteroatom-doped oxidation precursor.

[0054] The present application utilizes the gas flow of inert gas to drive the above-mentioned heteroatom compounds into the reaction chamber and deposit them on the surface of the oxidized asphalt for heteroatom doping. During the experiment, it was unexpectedly discovered that when the asphalt powder was uniformly oxidized and doped with nitrogen atoms by atomic vapor deposition, as the amount of nitrogen atom doping increased, when the above-mentioned asphalt-based hard carbon negative electrode material was used as the negative electrode material of the sodium ion battery, the reversible capacity of the battery showed a trend of first increasing and then decreasing, and the battery reversible capacity was the highest when the mass percentage of nitrogen atom doping was 0.2%. This may be because the increase in the amount of nitrogen atom doping allows the oxidation precursor to form a more complex network structure, effectively inhibiting the rearrangement of asphalt during the carbonization process, thereby significantly improving the sodium storage function of the asphalt-based hard carbon negative electrode material, as well as the electrochemical performance as a negative electrode material for sodium ion batteries; but at the same time, as the amount of nitrogen atom doping increased, the material structure was distorted, which weakened the sodium storage function of the asphalt-based hard carbon negative electrode material to a certain extent. On the other hand, as the amount of nitrogen atom doping increases, the battery's first efficiency shows an upward trend. The possible reason is that the increase in the amount of nitrogen atom doping can provide more active sites for lithium-ion batteries, increase the direct contact area between the electrode and the electrolyte, and facilitate the embedding and de-embedding of ions, thereby improving the battery's first efficiency.

[0055] In a preferred embodiment, the mass percentage of nitrogen atoms in the heteroatom-doped oxidation precursor is 0.1% to 0.4%.

[0056] In a more preferred embodiment, the mass percentage of nitrogen atoms in the heteroatom-doped oxidation precursor is 0.1% to 0.3%.

[0057] In the present application, the above-mentioned heteroatom compounds include compounds that can achieve nitrogen atom doping. The above-mentioned compounds have groups such as amino or cyano groups, which can be used as nitrogen sources to achieve in-situ doping of nitrogen atoms, adjust the structure and active sites of asphalt materials, etc. At the same time, the above-mentioned groups can produce volatile gases such as ammonia during the carbonization process, which is conducive to the formation of a porous structure and play a role in pore formation, comprehensively improving the sodium storage function of asphalt-based hard carbon negative electrode materials and improving their electrochemical performance. It should be understood that the above-mentioned compounds that can achieve nitrogen atom doping can be but are not limited to one or more of urea, ammonium citrate, dopamine, amino acids, cyanamide, dicyanamide, melamine and cyanuric acid.

[0058] In some embodiments, the heteroatom compound further includes at least one of a compound capable of phosphorus atom doping and a compound capable of sulfur atom doping, such as but not limited to one or more of phospholipids, thiophene, sulfur, thiourea, thiosulfate and thiol.

[0059] The present application does not limit the source of the above-mentioned asphalt powder. The above-mentioned asphalt powder can be a commercially available product, or it can be obtained by crushing asphalt. The above-mentioned crushing method can be other conventional crushing methods such as mechanical bead milling, impact, shearing and air flow impact. The present application has no special requirements for the above-mentioned asphalt, and asphalt known in the art can be used, such as but not limited to high softening point asphalt, medium softening point asphalt and low softening point asphalt. In some embodiments, the particle size of the above-mentioned asphalt powder is 5μm to 20μm, and the asphalt powder can be quickly, uniformly and fully oxidized by atomic vapor deposition.

[0060] In some embodiments, in step S1, the temperature of the oxidation treatment is 200°C to 400°C.

[0061] In some embodiments, in step S2, the protective atmosphere is an inert gas, and the gas of the protective atmosphere is at least one of nitrogen, argon, neon, helium, xenon or krypton.

[0062] In some embodiments, in step S2, the temperature of the carbonization treatment is 1100° C. to 1700° C., and the time of the carbonization treatment is 1 hour to 5 hours. It is understood that before the carbonization treatment, the oxidized precursor may be subjected to a pre-carbonization treatment, wherein the temperature of the pre-carbonization treatment may be, but not limited to, 700° C. to 900° C., and the time may be, but not limited to, 10 minutes to 30 minutes.

[0063] Based on this, the present application provides a asphalt-based hard carbon negative electrode material, which is prepared by the above-mentioned preparation method.

[0064] The present application also provides the use of the above-mentioned asphalt-based hard carbon negative electrode material in the preparation of sodium ion battery negative electrode material.

[0065] On the other hand, the present application also provides a battery, which includes a positive electrode and a negative electrode, wherein the negative electrode includes the above-mentioned asphalt-based hard carbon negative electrode material.

[0066] In some embodiments, the battery is a sodium ion battery.

[0067] It should be understood that materials of the same or similar type, model, quality, properties or functions as the reagents and instruments used in the following examples can be used to implement the present application. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples can be obtained from commercial sources unless otherwise specified.

[0068] The following are examples:

[0069] Example 1

[0070] The method for preparing the pitch-based hard carbon negative electrode material provided in this embodiment comprises the following steps:

[0071] (1) The asphalt is crushed to obtain asphalt powder with an average particle size of 8 μm.

[0072] (2) Place 30 g of asphalt powder in the cavity of an atomic layer deposition (ALD) device and use an atomic vapor deposition method according to the following steps: S21, nitrogen purge for 60 seconds; S22, introduce ozone for 120 seconds; S23, repeat steps S21 and S22 for 30 times in sequence; uniformly oxidize the asphalt powder at a temperature of 280°C to obtain an oxidized precursor.

[0073] (3) The above-mentioned oxidized precursor is placed in a nitrogen atmosphere at 1300° C. for 2 h for high-temperature carbonization treatment to obtain a pitch-based hard carbon negative electrode material.

[0074] The above-mentioned asphalt-based hard carbon negative electrode material is used as the negative electrode material of sodium ion battery and assembled into button cells. The specific assembly method is as follows: the above-mentioned asphalt-based hard carbon material is made into a slurry with conductive carbon black and a binder, and is evenly coated on an aluminum foil and dried to form an electrode. The sodium sheet is used as the counter electrode, and the diaphragm is a glass fiber film. A mixed solution of 1 mol / L NaPF6 and ethylene carbonate (EC): dimethyl carbonate (DEC) = 1:1 vol.% is used as the electrolyte to form a button cell. The first charge and discharge test is carried out by discharging to 0V at 0.1C (nominal capacity 200mA / g), and then charging to 2.5V to obtain the first discharge capacity and the first charge gram capacity. The constant current charge and discharge test is carried out at 0.1C, and the charge and discharge voltage range is 0V~2.5V. The cycle performance test is carried out at a constant temperature of 25°C. The first cycle charge reversible capacity and first efficiency of the above-mentioned battery are shown in Table 1, and the charge and discharge curves are shown in Table 1. Figure 2 shown.

[0075] Comparative Example 1

[0076] The preparation of the pitch-based hard carbon negative electrode material provided in this comparative example comprises the following steps:

[0077] (1) The asphalt is crushed to obtain asphalt powder with an average particle size of 13 μm.

[0078] (2) 30 g of asphalt powder was placed in a crucible and oxidized in a muffle furnace at 280° C. for 6 h under air atmosphere. After cooling to room temperature, an oxidized precursor was obtained.

[0079] (3) The above-mentioned oxidized precursor is placed at 1300°C for 2 hours for high-temperature carbonization treatment to obtain a pitch-based hard carbon negative electrode material.

[0080] The above-mentioned asphalt-based hard carbon negative electrode material was used as the negative electrode material for sodium ion batteries and assembled into button cells. The assembly method was the same as in Example 1, and the first-cycle charging reversible capacity and first efficiency thereof were tested. The results are shown in Table 1.

[0081] Example 2

[0082] The method for preparing the pitch-based hard carbon negative electrode material provided in this embodiment comprises the following steps:

[0083] (1) The asphalt is crushed to obtain asphalt powder with an average particle size of 5 μm.

[0084] (2) Place 30 g of the above-mentioned asphalt powder in the cavity of an atomic layer deposition device, and use an atomic vapor deposition method according to the following steps: S21, nitrogen purge for 60 seconds; S22, introduce ozone for 120 seconds; S23, introduce nitrogen carrying urea, and introduce urea into the reaction chamber by fluidization, and the reaction time is 5 seconds; S24, repeat steps S21, S22, and S33 for 30 times in sequence; uniformly oxidize the asphalt powder and dope it with nitrogen atoms at a temperature of 280°C to obtain a nitrogen atom-doped oxidized precursor with a nitrogen atom content of 0.1% by mass.

[0085] (3) The nitrogen atom-doped oxidized precursor is placed at 1300° C. for 2 h for high-temperature carbonization treatment to obtain a pitch-based hard carbon negative electrode material.

[0086] The above-mentioned asphalt-based hard carbon negative electrode material was used as the negative electrode material for sodium ion batteries and assembled into button cells. The assembly method was the same as in Example 1, and the first-cycle charging reversible capacity and first efficiency thereof were tested. The results are shown in Table 1.

[0087] Example 3

[0088] The method for preparing the pitch-based hard carbon negative electrode material provided in this embodiment comprises the following steps:

[0089] (1) The asphalt is crushed to obtain asphalt powder with an average particle size of 10 μm.

[0090] (2) Place 30 g of the above-mentioned asphalt powder in the cavity of an atomic layer deposition device, and use an atomic vapor deposition method according to the following steps: S21, nitrogen purge for 60 seconds; S22, introduce ozone for 120 seconds; S23, introduce an inert gas carrying ammonium citrate, and introduce the ammonium citrate into the reaction chamber by fluidization, and the reaction time is 5 seconds; S24, repeat steps S21, S22, and S33 for 60 times in sequence; uniformly oxidize the asphalt powder and dope it with nitrogen atoms at a temperature of 280°C to obtain a nitrogen atom-doped oxidized precursor with a nitrogen atom content of 0.2% by mass.

[0091] (3) The nitrogen atom-doped oxidized precursor is placed at 1300° C. for 2 h for high-temperature carbonization treatment to obtain a pitch-based hard carbon negative electrode material.

[0092] The above-mentioned asphalt-based hard carbon negative electrode material was used as the negative electrode material for sodium ion batteries and assembled into button cells. The assembly method was the same as in Example 1, and the first-cycle charging reversible capacity and first efficiency thereof were tested. The results are shown in Table 1.

[0093] Example 4

[0094] The method for preparing the pitch-based hard carbon negative electrode material provided in this embodiment comprises the following steps:

[0095] (1) The asphalt is crushed to obtain asphalt powder with an average particle size of 16 μm.

[0096] (2) Place 30 g of the above-mentioned asphalt powder in the cavity of an atomic layer deposition device, and use an atomic vapor deposition method according to the following steps: S21, nitrogen purge for 60 seconds; S22, introduce ozone for 120 seconds; S23, introduce an inert gas carrying melamine, and introduce melamine into the reaction chamber by fluidization, and the reaction time is 5 seconds; S24, repeat steps S21, S22, and S33 for 80 times in sequence; uniformly oxidize the asphalt powder and dope it with nitrogen atoms at a temperature of 280°C to obtain a nitrogen atom-doped oxidized precursor with a nitrogen atom content of 0.3% by mass.

[0097] (3) The nitrogen atom-doped oxidized precursor is placed at 1300° C. for 2 h for high-temperature carbonization treatment to obtain a pitch-based hard carbon negative electrode material.

[0098] The above-mentioned asphalt-based hard carbon negative electrode material was used as the negative electrode material for sodium ion batteries and assembled into button cells. The assembly method was the same as in Example 1, and the first-cycle charging reversible capacity and first efficiency thereof were tested. The results are shown in Table 1.

[0099] Example 5

[0100] The method for preparing the pitch-based hard carbon negative electrode material provided in this embodiment comprises the following steps:

[0101] (1) The asphalt is crushed to obtain asphalt powder with an average particle size of 8 μm.

[0102] (2) Place 30 g of the above-mentioned asphalt powder in the cavity of an atomic layer deposition device, and use an atomic vapor deposition method according to the following steps: S21, nitrogen purge for 60 seconds; S22, introduce ozone for 120 seconds; S23, introduce an inert gas carrying cyanamide, and introduce cyanamide into the reaction chamber by fluidization, and the reaction time is 5 seconds; S24, repeat steps S21, S22, and S33 for 90 times in sequence; uniformly oxidize the asphalt powder and dope it with nitrogen atoms at a temperature of 280°C to obtain a nitrogen atom-doped oxidized precursor with a nitrogen atom content of 0.4% by mass.

[0103] (3) The nitrogen atom-doped oxidized precursor is placed at 1300° C. for 2 h for high-temperature carbonization treatment to obtain a pitch-based hard carbon negative electrode material.

[0104] The above-mentioned asphalt-based hard carbon negative electrode material was used as the negative electrode material for sodium ion batteries and assembled into button cells. The assembly method was the same as in Example 1, and the first-cycle charging reversible capacity and first efficiency thereof were tested. The results are shown in Table 1.

[0105] Example 6

[0106] The method for preparing the pitch-based hard carbon negative electrode material provided in this embodiment comprises the following steps:

[0107] (1) The asphalt is crushed to obtain asphalt powder with an average particle size of 6 μm.

[0108] (2) Place 30 g of the above-mentioned asphalt powder in the cavity of an atomic layer deposition device, and use an atomic vapor deposition method according to the following steps: S21, nitrogen purge for 60 seconds; S22, introduce ozone for 120 seconds; S23, introduce an inert gas carrying urea, and introduce urea into the reaction chamber by fluidization, and the reaction time is 5 seconds; S24, repeat steps S21, S22, and S33 100 times in sequence; uniformly oxidize the asphalt powder and dope it with nitrogen atoms at a temperature of 280°C to obtain a nitrogen atom-doped oxidized precursor with a nitrogen atom content of 0.5% by mass.

[0109] (3) The nitrogen atom-doped oxidized precursor is placed at 1300° C. for 2 h for high-temperature carbonization treatment to obtain a pitch-based hard carbon negative electrode material.

[0110] The above-mentioned asphalt-based hard carbon negative electrode material was used as the negative electrode material for sodium ion batteries and assembled into button cells. The assembly method was the same as in Example 1, and the first-cycle charging reversible capacity and first efficiency thereof were tested. The results are shown in Table 1.

[0111] Table 1 Performance of batteries assembled in Examples 1 to 6 and Comparative Example 1

[0112] First cycle reversible capacity (mAh / g) First efficiency (%) Example 1 300.33 88.71 Comparative Example 1 283.68 86.62 Example 2 313.29 86.03 Example 3 321.72 87.46 Example 4 310.52 87.43 Example 5 302.83 88.32 Example 6 283.57 88.41

[0113] From the test results in Table 1, it can be seen that by comparing Example 1 with Comparative Example 1, it can be seen that compared with the traditional oxidation method, the present application adopts the atomic vapor deposition method to oxidize the asphalt, directly cross-links with ozone, and forms a cross-linked structure between the asphalts, which can ensure uniform oxidation of the asphalt, inhibit the rearrangement of the asphalt in the subsequent carbonization process, and obtain disordered hard carbon, thereby improving the sodium storage function of the asphalt-based hard carbon negative electrode material. When the asphalt-based hard carbon negative electrode material prepared in the above embodiment is applied to a sodium ion battery, the reversible capacity and initial efficiency of the battery can be improved ( Figure 2 ), which has the advantages of high platform capacity and stable cycle performance.

[0114] In Examples 2 to 6, based on Example 1, nitrogen atoms are doped while oxidizing the asphalt by atomic vapor deposition, and the mass percentage of nitrogen atoms doped is 0.1% to 0.5%. The experiment found that the doping of nitrogen atoms can significantly improve the sodium storage function of the asphalt-based hard carbon negative electrode material. As the amount of nitrogen atoms doped increases, the reversible capacity of the battery shows a trend of first increasing and then decreasing. When the mass percentage of nitrogen atoms doped is 0.2%, the reversible capacity of the battery is the highest. This may be because the increase in the amount of nitrogen atoms doped makes the oxidation precursor form a more complex network structure, effectively inhibiting the rearrangement of asphalt during the carbonization process, thereby significantly improving the sodium storage function of the asphalt-based hard carbon negative electrode material and the electrochemical performance as a negative electrode material for sodium ion batteries; but at the same time, as the amount of nitrogen atoms doped increases, the material structure is distorted, which weakens the sodium storage function of the asphalt-based hard carbon negative electrode material to a certain extent, but its electrochemical performance such as sodium storage function or first efficiency is still higher than that of the asphalt-based hard carbon negative electrode material prepared by the traditional oxidation method.

[0115] In summary, compared with the existing preparation methods, the present application can achieve rapid and uniform oxidation of asphalt without introducing other heteroatoms and without the need for additional elution and impurity removal processes. It has the advantages of simple process, easy operation, and low cost, and provides convenience for the structure-activity relationship of asphalt-based hard carbon negative electrode materials.

[0116] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for preparing a pitch-based hard carbon negative electrode material, characterized in that: The steps include: S1. placing asphalt powder in a reaction chamber, then introducing inert gas and ozone in turn and repeating the cycle, oxidizing the asphalt powder by atomic vapor deposition to obtain an oxidized precursor; S2. Carbonizing the oxidative precursor in a protective atmosphere to obtain a pitch-based hard carbon negative electrode material.

2. The preparation method according to claim 1, characterized in that: The oxidation precursor is a heteroatom-doped oxidation precursor, and the heteroatom includes a nitrogen atom; The method for preparing the heteroatom-doped oxidative precursor comprises the following steps: S11, introducing inert gas to clean the reaction environment; S12, introducing ozone; S13, introducing an inert gas carrying a heteroatom compound; S14. Repeat steps S11, S12 and S13 in sequence to achieve uniform oxidation and heteroatom doping of the asphalt powder, and obtain a heteroatom-doped oxidation precursor, in which the mass percentage of nitrogen atoms is 0.1% to 0.5%.

3. The preparation method according to claim 2, characterized in that: In step S13, the heteroatom compound includes one or more of urea, ammonium citrate, dopamine, amino acid, cyanamide, dicyanamide, melamine and cyanuric acid.

4. The preparation method according to claim 2, characterized in that: In step S14, the mass percentage of nitrogen atoms in the heteroatom-doped oxidized precursor is 0.1% to 0.4%.

5. The preparation method according to claim 1, characterized in that: In step S1, the particle size of the asphalt powder is 5 μm to 20 μm.

6. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the oxidation treatment is 200°C to 400°C.

7. The preparation method according to claim 1, characterized in that: In step S2, the protective atmosphere gas is one or more of nitrogen, argon, neon, helium, xenon or krypton; And / or, the temperature of the carbonization treatment is 1100° C. to 1700° C., and the time is 1 hour to 5 hours.

8. A pitch-based hard carbon negative electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the asphalt-based hard carbon negative electrode material as claimed in claim 8 in the preparation of negative electrode materials for sodium ion batteries.

10. A battery, characterized in that: It comprises a positive electrode and a negative electrode, wherein the negative electrode comprises the pitch-based hard carbon negative electrode material as claimed in claim 8.

Citation Information

Patent Citations

  • Preparation method of three-dimensional connected heteroatom doped carbon nanosheet

    CN111661836A

  • Oxidized asphalt-based hard carbon negative electrode material for sodium-ion battery and preparation method of oxidized asphalt-based hard carbon negative electrode material

    CN115991467A

  • Heteroatom-doped porous hard carbon negative electrode material and preparation method and application thereof

    CN118289737A

Cited By

  • Sodium-ion battery hard carbon material and preparation method thereof

    CN122380342A